2020
DOI: 10.1007/s11019-020-09969-w
|View full text |Cite
|
Sign up to set email alerts
|

«If you give them your little finger, they’ll tear off your entire arm»: losing trust in biobank research

Abstract: Why do some people withdraw from biobank studies? To our knowledge, very few studies have been done on the reflections of biobank ex-participants. In this article, we report from such a study. 16 years ago, we did focus group interviews with biobank participants and ex-participants. We found that the two groups interestingly shared worries concerning the risks involved in possible novel uses of their biobank material, even though they drew opposite conclusions from their worries. Revisiting these interviews to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The conducted research confirmed the relationship between the willingness to donate biological material to a biobank and trust, selected preferred values and other specific personal features. Earlier research has also suggested a relationship between donation and trust in the context of biobanking [ 18 , 30 , 31 , 45 ]. Our research, however, revealed that not only general trust in people was important but specific kinds of trust, such as trust in scientists and doctors, play a more important role.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The conducted research confirmed the relationship between the willingness to donate biological material to a biobank and trust, selected preferred values and other specific personal features. Earlier research has also suggested a relationship between donation and trust in the context of biobanking [ 18 , 30 , 31 , 45 ]. Our research, however, revealed that not only general trust in people was important but specific kinds of trust, such as trust in scientists and doctors, play a more important role.…”
Section: Discussionmentioning
confidence: 99%
“…In our review of 61 previous social research studies, it was found that donation is a complex process that may be determined by psychosocial factors such as people’s knowledge and positive opinions of biobanks, trust, beliefs about the expected benefits, access to information about the research, donors’ cultural and religious beliefs and privacy protection [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. A few studies reported donors’ motivations [ 27 , 28 , 29 , 30 , 31 ]. It is also known that knowledge about psychosocial attitudes toward biobanking may increase the effectiveness of the recruitment process [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our ndings here report on the participants' experiences and thoughts on how CO90s engaged with them and the resultant relationship and trust they developed for it. This kind of trust that participants develop for their longitudinal cohort studies has been mentioned elsewhere [37] including in other studies [38] such as the Irish Longitudinal Study of Ageing (TILDA) which reported that their participants felt they had a bond with the study and a special rapport with data collectors and that this impacted on participant retention [39]. Consistent with previous writings [40] we have evidenced here that cohort study participation should not be considered a unidirectional activity, the interviews reported here demonstrate that the perceived reciprocity contributed to sustaining the long-term commitment required for a longitudinal study.…”
Section: Discussionmentioning
confidence: 75%
“…Our findings here report on the participants’ experiences and thoughts on how CO90s engaged with them and the resultant relationship and trust they developed for it. This kind of trust that participants develop for their longitudinal cohort studies has been mentioned elsewhere [ 58 ] including in other studies [ 59 ] such as the Irish Longitudinal Study of Ageing (TILDA) which reported that their participants felt they had a bond with the study and a special rapport with data collectors and that this impacted on participant retention [ 60 ]. Consistent with previous writings [ 30 ] we have evidenced here that cohort study participation should not be considered a unidirectional activity, the interviews reported here demonstrate that the perceived reciprocity contributed to sustaining the long-term commitment required for a longitudinal study.…”
Section: Discussionmentioning
confidence: 96%